Gender, social networks and peformance - Ilse Lindenlaub; Anja Prummer (Queen Mary University of London, School of Economics and Finance, 2016)
This paper documents gender differences in social ties and develops a theory that links them to disparities in men's and women's labor market performance. Men's networks lead to better access to information, women's to higher peer pressure. Both affect effort in a model of teams, each beneficial in different environments. We find that information is particularly valuable under high uncertainty, whereas peer pressure is more valuable in the opposite case. We therefore expect men to outperform women in jobs that are characterized by high earnings uncertainty, such as the financial sector or film industry - in line with the evidence.
Keywords: D85; Z13; J16; 330; Networks; Peer pressure; Gender; Labor market outcomes